Comparison of the hydrodynamic profile between competitive triathletes and swimmers - Assiria-Costa, L.; Machado, M. L.; Santos, C. C.; Costa, M. J. (Journal of Functional Morphology and Kinesiology, 2026)
Objectives: This study aimed to compare the hydrodynamic profile between triathletes and competitive swimmers and to establish associations with short- and middle-distance performance.